'What works here doesn't work there': The significance of local context for a sustainable and replicable asset‐based community intervention aimed at promoting social interaction in later life. (12th March 2019) - Wildman, Josephine M.; Valtorta, Nicole; Moffatt, Suzanne; Hanratty, Barbara
Abstract: Interventions that harness local assets to benefit a community are increasingly being promoted to improve health and well‐being. In practice, we know little about how local contexts or reliance on local resources affect the sustainability and scalability of asset‐based community developments. This qualitative case study documents the development and implementation of a novel asset‐based community development project. Based in a large mainly rural county in North East England with relatively high levels of socioeconomic deprivation, the project aimed to prevent social isolation among older people, using a range of food‐related activities. Twenty‐one semi‐structured interviews were conducted with service users, volunteers, project partners, project development workers and senior staff. Interviews explored the project's design and implementation process, outcomes for participants and the wider community, and project sustainability and scalability. Thematic analysis of the data identified four factors likely to be important for creating sustainable and replicable asset‐based community projects. These factors are (a) recognising and harnessing assets among local people who may be otherwise marginalised due to age, geographical isolation and/or socioeconomic deprivation; (b) identifying assets that can be provided by local businesses; (c) genuine project co‐production to develop activities that meet local needs and inspire enthusiasm among all stakeholders; and (d) ongoing organisational support to meet the challenges to sustainability that exist in socioeconomically deprived areas. We conclude that successful asset‐based community projects require extensive community input and learning captured from existing programmes can facilitate the replicability of programmes in other community contexts.